Anticancer and anti-inflammatory properties of mangiferin: A review of its molecular mechanisms - Mei, Suhuan; Ma, Haile; Chen, Xiumin (Food and chemical toxicology, 2021)
Chronic inflammation is crucial for the pathological process of tumors due to increasing the infiltration of cytokines, growth factors, and chemokines to the tumor microenvironment. Phenolic compounds are considered natural remedies for inflammation and cancer. Mangiferin is a C-glycosyl xanthone that possesses numerous pharmacological activities. It has the potential to attenuate inflammation in different organs through the mechanisms of inhibiting pattern recognition receptors, regulating cell signaling pathways, activating autophagy, inhibiting the secretion of inflammatory mediators, and protecting intestinal barrier integrity, which in turn prevents cancer. In this review, the recent advances in the anti-inflammation and anti-cancer mechanisms of mangiferin as well as its safety and toxicity were summarized. The impacts of modified mangiferin and the synergic effects with other components were also discussed. Understanding the molecular targets of mangiferin is of great significance for its better application in the amelioration of inflammation-related diseases. [Display omitted] •Mangiferin has the potential to attenuate inflammation in different organs.•Mangiferin regulates receptors, cell signalings, and cytokines.•Mangiferin activates autophagy and protects intestinal barrier integrity.•Mangiferin shows potential therapeutic capability for inflammation-related cancer.•A dose of mangiferin less than 2 g/kg BW/day is generally considered safe.